Dwelling in the world : family, house, and home in Tianjin, China, 1860-1960 - LaCouture, Elizabeth (Studies of the weatherhead East Asian institute, 2021)
"Dwelling in the World writes the history of the modern home into the history of modern China, arguing that during the first half of the 20th century, Chinese urban elites invented the modern home by drawing on a variety of global and local discourses, practices, and styles. This book re-frames modern Chinese social and cultural history, typically described in terms of national awakening, in a global context, while also challenging Euro-American historical notions that the modern private sphere was a natural development of industrialization. The author argues that home became a contact zone of foreign and domestic in which Chinese people developed new forms of social distinction, creating a new urban cosmopolitan class. Dwelling in the World focuses on a single city: the northern city Tianjin, a former Qing regional administrative city that became a treaty-port in 1860 and eventually home to nine foreign-controlled municipal districts or concessions. Tianjin's multiple foreign empires deconstructed and altered the urban landscape, unraveling Qing imperial authority in the built environment and re-orienting Chinese people and trade to a new global stage of multiple empires. After the Qing collapsed in 1911, Tianjin no longer had a single political center, and the Chinese household, once the cornerstone of the imperial order, became a contested material and social space. These changes allowed Chinese people to shape everyday life for themselves. After World War II Tianjin became a wholly Chinese city again, the Guomindang municipal government finally proposed a plan for public housing, and later, the post-1949 Communist government made housing a top priority. But as housing became a citizen's right guaranteed by Communism, Chinese people no longer had the space to define home for themselves. By opening the door to modern Chinese housing, the Communists had closed the door on the cosmopolitan home"--